2017
DOI: 10.1111/pde.13177
|View full text |Cite
|
Sign up to set email alerts
|

Atenolol Versus Propranolol for Treatment of Infantile Hemangiomas During the Proliferative Phase: A Retrospective Noninferiority Study

Abstract: Our study supports previous findings that atenolol is at least as effective as propranolol for treatment of IHs and poses less risk of bronchospasm. Our SCAMP proposes guidelines for dosing and monitoring parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
54
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 16 publications
2
54
0
4
Order By: Relevance
“…We stated that expression of IL-6 and CLCF1 is regulated by hsa-mir-34a, which is broadly described in the context of influence on the pluripotentiality of stem cells. 8 We also observed overexpression of the IFNR1 receptor, participating in the activation of the interferon-dependent path, which is responsible for the occurrence of paradoxical psoriasis during anti-TNF medicine therapy. 9 Such observation may partially explain the occurring loss of response in the therapy with the use of TNF inhibitors and constitute the basis to elaborate a new therapeutic strategy.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…We stated that expression of IL-6 and CLCF1 is regulated by hsa-mir-34a, which is broadly described in the context of influence on the pluripotentiality of stem cells. 8 We also observed overexpression of the IFNR1 receptor, participating in the activation of the interferon-dependent path, which is responsible for the occurrence of paradoxical psoriasis during anti-TNF medicine therapy. 9 Such observation may partially explain the occurring loss of response in the therapy with the use of TNF inhibitors and constitute the basis to elaborate a new therapeutic strategy.…”
mentioning
confidence: 67%
“…5 Atenolol is a hydrophilic selective beta-1 blocker and a few studies have already indicated that it has similar effects on IHs compared with propranolol and fewer adverse effects, demonstrating a favourable risk-benefit profile. 2,[6][7][8] We performed a comparative study, in order to evaluate the efficacy and safety of treatment, between a group of infants with hemangiomas who received atenolol (n = 26) and a previously described group of infants in our department, who received propranolol for the treatment of their hemangiomas (n = 28). 9,10 Infants with problematic IHs during the proliferative phase were considered for inclusion in both studies.…”
mentioning
confidence: 99%
“…After full‐text review of the remaining 60 records, 51 articles were removed according to the exclusion criteria. Nine studies were included in the final analysis. These nine studies included three research letters with clear descriptions of the original data, two retrospective studies, one prospective study, one cohort study and two RCT .…”
Section: Resultsmentioning
confidence: 99%
“…The authors reported excellent response with no side effects. Subsequently, several studies have reported their experience in using oral atenolol in IH, especially as an alternative to propranolol …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, undesirable side effects, although rare, may force the temporary interruption or complete cessation of propranolol, as demonstrated in our case. Recently, interest in alternative selective beta‐blockers, such as atenolol, has been proposed, revealing similar efficacy as propranolol but with a safer profile as far as concerns with respiratory side effects . Atenolol as a selective beta‐1 antagonist avoids several side effects such as bronchospasm and, as a hydrophilic molecule, does not cross the brain barrier, avoiding sleep disturbances .…”
mentioning
confidence: 99%